Potential of bio-metal cutting fluid from treated recycled cooking oil for metal cutting fluid application / Ahsana Aqilah Ahmad, Jaharah A. Ghani and Che Hassan Che Haron - Ahmad, Ahsana Aqilah; A. Ghani, Jaharah; Che Haron, Che Hassan (Universiti Teknologi MARA, 2022)
Metalworking Fluids (MWFs) are extensively used to achieve a smoother machining operation, a better surface finish, and a longer tool life. Unfortunately, mineral-based metalworking fluids have negative impacts on the workers as well as the environment. This study focuses on the application of bio-MWF from treated recycled cooking oil (TRCO) in machining alloy steel (AISI 4340) metal as a case study. The TRCO from the oil-palm base is proposed due to its availability and not suitable to be consumed by humans. The minimum quantity lubrication (MQL) experimented for machining AISI 4340 with machining parameters recommended for finishing operation at a high-speed regime of machining AISI 4340. The results of cutting force and surface roughness were found to improve compared to dry cutting. Lower cutting force and good surface roughness were obtained. The chips collected from MQL cutting were also thinner and curlier compared to dry cutting which indicates lower friction occurred during the cutting process. The findings from this study indicate TRCO is suitable and has a good potential to be utilized as metal cutting fluid and it supports the Malaysian government policy to create a sustainable environment manufacturing process.